Synthesis and evaluation of novel 4-anilinocoumarin derivatives as potential antimicrobial agents - Sonia Yadav, Nitin Kumar, Vijay Bhalla (Journal of Applied Pharmaceutical Science, 2022)
The development of potential antimicrobial agents is one of the critical needs to obviate microbial infection. Coumarins are acknowledged as the potential therapeutic regime for several ailments including microbial infection. Due to the microbial resistance of the existing pharmaceuticals, the present aim of the study is associated with the development of novel 4-anilinocoumarins and their exploration against several Gram-positive and negative microbial stains. A series of 4-anilinocoumarins derivatives was synthesized through Schiff base reaction and characterized by mass spectrometric, FT-IR, and 1 HNMR analytical techniques. Antibacterial activity of each synthesized compound was determined against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeureginosa. The results showed that compound 4a’, 4d’, and 4h’ were showing significant (p < 0.05) inhibitory action with average zones of inhibition: 5.905 ± 1.011, 6.145 ± 1.138, and 6.595 ± 0.021 mm against S. aureus; 4.82 ± 0.042, 3.97 ± 0.014, and 5.335 ± 0.021 mm against B. subtilis; 3.8 ± 0.056, 5.805 ± 0.728, and 3.755 ± 0.091 mm against E. coli; and 5.51 ± 0.381, 5.61 ± 0.001, and 5.66 ± 0.014 mm inhibition, respectively. Hence, it can be demonstrated that 4-anilinocoumarins exhibit the potential role as antimicrobial agents.
Keywords: Coumarins, 4-anilinocoumarin derivatives, spectral analysis, antibacterial activity.